Study on optimization of exhaust gas purification device and CO catalytic elimination of industrial transport vehicles - Xiaoyu Chen; Yating Liu; Jiaxin Shi; Le Li; Shuo Gao; Junyi Li; Jia Li; Yu Zhang; Yichao Lin (Fuel Processing Technology)
To address the issue of excessive CO emissions in the exhaust of explosion-proof diesel vehicles used in mining operations, this study developed and optimized an exhaust CO purification device featuring a Co3O4 monolithic catalyst core. The internal structure and external water-cooling system of the device were refined through numerical simulation. Field tests demonstrated that when the vehicle was equipped with the exhaust gas purification device, the maximum CO removal efficiency reached 97.7 %. During underground operations, the highest CO purification efficiency reached 64 %, while during coal shoveling activities, the average CO purification efficiency was 52.2 %. The device is of great significance for improving the underground working environment and ensuring the life, health and safety of personnel.